Beyond the Binary: Intraracial Diversity in Family Organization and Black Adolescents' Educational Performance. (8th September 2021) - Cross, Christina J
Abstract: Using a nationally representative sample of African American adolescents from the National Survey of American Life Adolescent supplement (NSAL-A), this study examines intraracial diversity in two key dimensions of family organization—family structure and family integration—and assesses their relationship with youths' educational performance, namely, grades, grade repetition, and number of suspensions. Results show that there is substantial within-group heterogeneity in family organization among African Americans, and that patterns of organization vary systematically by level of household resources, specifically household income. Results also indicate that the relationship between family structure and family integration and Black adolescents' educational performance differs by resource level. These factors are generally unrelated to the grades, grade repetition, and number of suspensions of adolescents from low-income households, but they are associated with these outcomes for adolescents from the most economically advantaged households. Irrespective of household income, findings demonstrate that the substantive impact of family organization on Black youths' educational outcomes is small, which suggests that family organization has a more limited relationship with Black Americans' life chances than previously theorized.